Role Of Catalysis In The Decomposition Of Volatile Organic Componds (VOC) In Air Stream. - Abdullah, Ahmad Zuhairi; Bakar, M Zailani Abu; Bhatia, Subhash (2002)
This article reviews the role of catalysts for catalytic decomposition of VOC in air.